2013
DOI: 10.1186/2228-5326-3-44
|View full text |Cite
|
Sign up to set email alerts
|

Morphology dependence on anions in hydrothermal synthesis of Co3O4

Abstract: One-dimensional (1D) nanostructures of Co 3 O 4 were synthesized via a mild hydrothermal route. The results of XRD, IR, and TEM revealed a phase transformation was accompanied by the replacement of NO 3 − with CO 3 2− throughout the hydrothermal process. The symmetric types and amount of NO 3 − and CO 3 2− intercalated between the brucite layers played an important role in the formation of nanowires from the hydrothermal system. The amount of CO 3 2− increased as the hydrothermal reaction proceeded. The substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The broad absorption peak at 3150–3520 cm −1 is the stretched vibration of physically adsorbed water, while the bending vibration of physically adsorbed water appears at 1630 cm −1 . The spectrum of Ni/SFCCC absorption peaks at 1390 and 823 cm −1 indicate the presence of NO 3 ‐ and the absorption band for the Si–H stretching vibration is observed at 2350 cm −1 . Additionally, there are no changes in the structure of SFCCC and Ni/SFCCC.…”
Section: Resultsmentioning
confidence: 98%
“…The broad absorption peak at 3150–3520 cm −1 is the stretched vibration of physically adsorbed water, while the bending vibration of physically adsorbed water appears at 1630 cm −1 . The spectrum of Ni/SFCCC absorption peaks at 1390 and 823 cm −1 indicate the presence of NO 3 ‐ and the absorption band for the Si–H stretching vibration is observed at 2350 cm −1 . Additionally, there are no changes in the structure of SFCCC and Ni/SFCCC.…”
Section: Resultsmentioning
confidence: 98%
“…The bands at 3756 cm −1 , 3652 cm −1 and 1640 cm −1 were assigned to asymmetric stretching, symmetrical stretching and bending vibrations of physically absorbed water. The vibration peaks of NO 3 − at 1382 cm −1 and 823 cm −1 [ 33 ] were not observed, which suggested that the nitrates on the catalyst were completely decomposed after calcination.
Figure 7.
…”
Section: Resultsmentioning
confidence: 99%
“…Co3O4 nanocrystals have also been synthesized via a facile combustion method by Feng et al [29]. Beside these several other methods have also been used for the synthesis of spinel Co3O4 nanocrystals such as sol-gel method, polyol process, solvothermal synthesis, polymer assisted synthesis, thermal decompositions, reflux/microwave assisted methods and hydrothermal synthesis for Co3O4 nanorods [30,23,[31][32][33][34][35][36]. All these methods produce high quality nanostructure with different morphologies, but the requirement of high temperature limits the compatibility of growth e.g.…”
Section: Introductionmentioning
confidence: 99%